State and Legal Regulation of the Investment Process - Qoqiauri, L.; Gechbaia, B.; Кокіаурі, Л.; Гечбаія, Б. (КНТУ, 2016)
Complex state investment policy, directed towards creation of advantage investment surrounding in the country, its regions and fields of industrial production, essentially grows inflow of investment resources into theeconomy. Therefore the necessity to optimize the state legal regulation of the investment process is raised on the foreground in this work. It has been substantiated that searching of new state instruments of regulation is necessary in the investment domain. Комплексна державна інвестиційна політика, спрямована на створення переваг в інвестиційному середовищі країни, її регіонів та сферах промислового виробництва, дозволяє суттєво збільшити приток інвестиційних ресурсів в економіку. Відповідно на перший план в роботі піднімаються питання необхідності оптимізації державного правового регулювання інвестиційного процесу.
Державне та правове регулювання інвестиційного процесу
Keywords: investment; investment laws; investment regulation; foreign investment; investment business; financial investment; investment policy; financial assets; investment market; portfolio investments; resources; investment planning; бізнес; фінансові інвестиції; інвестиційна політика; інвестиційний ринок; фінансові активи; ресурси; портфельні інвестиції; інвестиційне планування інвестиції; інвестиційне законодавство; регулювання інвестицій; іноземні інвестиції